Red cell distribution width (RDW) as a predictor of long-term mortality in patients undergoing percutaneous coronary intervention - Poludasu, Shyam; Marmur, Jonathan D.; Weedon, Jeremy; Khan, Waqas; Cavusoglu, Erdal (Thrombosis and Haemostasis, 2009)
Red cell distribution width (RDW) has been shown to be an independent predictor of mortality in patients with coronary artery disease and in patients with heart failure. The current study evaluated the prognostic utility of RDW in patients undergoing percutaneous coronary intervention (PCI). We evaluated 859 patients who underwent PCI during January 2003 to August 2005. After a median follow up of four (interquartile range 3.1 to 4.4) years, there were a total of 95 (11%) deaths. RDW was analysed as a categorical variable with empirically determined cut points of 13.3 and 15.7 (low RDW <13.3, medium RDW ≥13.3 to <15.7, high RDW ≥15.7) based on differences in hazard ratio (HR) for death among RDW deciles.In univariate analysis, higher RDW was a significant predictor of mortality (p<0.001). In multivariate analysis there was a significant two-way interaction between RDW and haemoglobin (Hgb). RDW was not an independent predictor of mortality in patients with Hgb <10.4. However, among patients with Hgb >10.4, high RDW was a strong and independent predictor of mortality. For patients with Hgb ≥10.4 to <12.7, HR for death in patients with high RDW relative to low RDW was 5.2 (95% confidence intervals [CI]: 2.0–13.3). For patients with Hgb ≥12.7, HR for death in patients with high RDW relative to low RDW was 8.6 (CI:2.8–28.6). Higher RDW was a strong and independent predictor of long-term mortality in patients undergoing PCI who were not anaemic at baseline.
Keywords: Red cell distribution width (RDW); percutaneous coronary intervention; mortality